2012
DOI: 10.1097/qai.0b013e318246538f
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Tuberculosis Diagnostic Strategies to Reduce Early Mortality Among Persons With Advanced HIV Infection Initiating Antiretroviral Therapy

Abstract: Our analysis showed that culture or Xpert were cost-effective at reducing early mortality during the first 6 months of ART compared with the current practice. Thus, our findings provide support for ongoing efforts to expand TB diagnostic capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…A physician's decision, based on a clinical work-up of symptoms, chest X-ray (CXR), and sputum smear microscopic examination, triggers the TB treatment at district level hospitals within the developing setting of Southeast Asia, where culture is usually not included in the routine diagnosis algorithm [17]. Recently, the WHO-recommended TB diagnosis models were compared in HIV-infected TB suspects, in terms of cost effectiveness, to reduce the mortality within 6 months of antiretroviral therapy (ART) initiation [18]. The GeneXpert algorithm was found to be less costly than either smear-CXR or smear-CXR-culture algorithms.…”
Section: Diagnosis Of Active Tb Disease In Hiv-infected Personsmentioning
confidence: 99%
See 1 more Smart Citation
“…A physician's decision, based on a clinical work-up of symptoms, chest X-ray (CXR), and sputum smear microscopic examination, triggers the TB treatment at district level hospitals within the developing setting of Southeast Asia, where culture is usually not included in the routine diagnosis algorithm [17]. Recently, the WHO-recommended TB diagnosis models were compared in HIV-infected TB suspects, in terms of cost effectiveness, to reduce the mortality within 6 months of antiretroviral therapy (ART) initiation [18]. The GeneXpert algorithm was found to be less costly than either smear-CXR or smear-CXR-culture algorithms.…”
Section: Diagnosis Of Active Tb Disease In Hiv-infected Personsmentioning
confidence: 99%
“…The GeneXpert algorithm was found to be less costly than either smear-CXR or smear-CXR-culture algorithms. Culture and GeneXpert algorithms were more cost effective in reducing mortality than the current practice [18] (Table). This report represented a new diagnostic outline, skipping traditional diagnosis methods, which is likely to save time and resources.…”
Section: Diagnosis Of Active Tb Disease In Hiv-infected Personsmentioning
confidence: 99%
“…Other studies have found that Xpert *Address correspondence to Catharina C. Boehme, 16, Av de BudĂ© , Geneva 1202. E-mail: Catharina.Boehme@finddiagnostics.org MTB/RIF testing was cost-effective for reducing premature mortality in patients with advanced HIV infection, both at the time of presentation with TB symptoms, 13 and before initiation of antiretroviral therapy.…”
Section: How a New Tool Fits Inmentioning
confidence: 99%
“…Many model-based economic evaluations, [5][6][7] predicted that Xpert would be cost-effective, either through a reduction in tuberculosis-related mortality or reduction in the overtreatment of tuberculosis, or both, in a wide range of settings. Nevertheless, concerns over cost-effectiveness remained and the WHO guideline recommendation was conditional, explicitly acknowledging potential resource implications.…”
Section: Introductionmentioning
confidence: 99%